"Pouring Jewish water into fascist wine" / Volume 2 - Maryks, Robert A. ("Pouring Jewish water into fascist wine" untold stories of (Catholic) Jews from the archive of Mussolini's Jesuit Pietro Tacchi Venturi, 2017)
The aim of the second part of the project on the impact of the racial laws under the Mussolini regime is to offer the reader a critical edition and an English translation of 139 letters that were exchanged between the victims of those laws (and their relatives and friends) and the Jesuit Pietro Tacchi Venturi (1861?1956) who interceded with the Fascist government in order to circumvent or alleviate various provisions of the 1938 anti-Jewish legislation